PENENTUAN LOKASI PEMBANGUNAN PERUMAHAN: PENERAPAN ANALYTIC HIERARCHY PROCESS (AHP) DI KOTA MALANG - , M. Achsin ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Location desicion is an important strategy for many firm because it is difficult and expensive activity. Location desicion requires many factor which need qualitative and quantitative consideration. Analytic Hierarchy Process (AHP) is a method of decision-making that the main tool is the hierarchy. With a hierarchy, a complex and unstructured problem will be divided, grouped and arranged into a form of hierarchy. The main data of AHP model is human perception that considered an expert. With the AHP model, this thesis is to answer what criteria are used by the developer in choosing the location of housing in the region of Malang. There are four criteria, with respective are identified, these are: (1) Economic Criteria, the following sub criteria are (a) land prices, (b) development cost, (c) proximity to sources of labour, (d) availability/affordability of water sources, and (e ) availability/affordability of electrical fasilities